2002
DOI: 10.2170/jjphysiol.52.41
|View full text |Cite
|
Sign up to set email alerts
|

Frequency Distribution, Variance, and Moving Average of Left Ventricular Rhythm and Contractility during Atrial Fibrillation in Dog.

Abstract: Many groups in both basic and clinical studies [1][2][3][4][5][6][7][8][9] have long investigated basic statistical characteristics, including the frequency distribution of arrhythmic beat interval (RR), during atrial fibrillation (AF). Mean RR has been used to evaluate the average RR during AF [9][10][11]. However, the minimal number of beats from which the mean RR has been reliably obtained varied widely between only 4 beats to as many as the number of beats for 2 min among investigators and their purposes [… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
27
0

Year Published

2005
2005
2008
2008

Publication Types

Select...
6

Relationship

5
1

Authors

Journals

citations
Cited by 6 publications
(28 citation statements)
references
References 27 publications
1
27
0
Order By: Relevance
“…Figure 1 illustrates these variables under AF in the P-V diagram. We have described in detail the methods to calculate EW, E max , and PVA elsewhere [7,8]. Briefly, we first obtained V 0 ( Fig.…”
Section: Mechanoenergetic Variablesmentioning
confidence: 99%
See 3 more Smart Citations
“…Figure 1 illustrates these variables under AF in the P-V diagram. We have described in detail the methods to calculate EW, E max , and PVA elsewhere [7,8]. Briefly, we first obtained V 0 ( Fig.…”
Section: Mechanoenergetic Variablesmentioning
confidence: 99%
“…We also calculated PVA as usual on a computer as the P-V area scanned by the instantaneous P-V line connecting the instantaneous P-V point to V 0 in each arrhythmic beat [7,8]. This calculation also yielded EW and PE (shaded rectangular and triangular areas, respectively, in Fig.…”
Section: Mechanoenergetic Variablesmentioning
confidence: 99%
See 2 more Smart Citations
“…We found them to skew enough to account for the rightward skewed frequency distribution of the EW/PVA during AF with the unexpectedly high mean EW/PVA. These results indicate that the LV arrhythmia during AF per se does not directly suppress the mean level of LV mechanical efficiency in normal canine hearts.Key words: heart, arrhythmia, external work, pressure-volume area.We have been investigating the statistical characteristics of major mechanoenergetic variables of the left ventricle (LV) beating arrhythmically during atrial fibrillation (AF) in normal canine in situ hearts [1][2][3][4][5][6]. In these studies, we have found the positive correlation between E max and the preceding beat interval [5]; the apparently nonnormal or non-Gaussian frequency distributions of the beat interval, heart rate, and effective arterial elastance (E a ) [1,2]; and the normal or Gaussian distributions of the end-systolic pressure-volume (P-V) ratio or maximal elastance (E max ) as a load-independent contractility index and the systolic P-V area (PVA) as a measure of the LV total mechanical energy [3,7].…”
mentioning
confidence: 99%